Development and evaluation of bio-organic composite manure for vegetables - Vipitha V P (Department of Agronomy, College of Agriculture, 2011)
An investigation entitled “ Development and evaluation of bio-organic composite manure for vegetables” was taken up at College of Agriculture, Vellyani during the period 2009-2011 . the main objective of the experiment was to assess the possibility of developing good quality bio-organic composite manure for organic vegetable production. The investigation was taken up in three stages namely, formulation and quality evaluation of bio organic composite manures, mineralization study of bio organic composite manures and crop response study. In the first experiment, study was conducted in the laboratory. Organic sources used for the preparation of bio organic composite manures were coir pith compost, poultry manure, neem cake, ground nut cake, ash, rock dust and microbial consortium. Raw materials collected from different parts of Kerala were analyzed and best sources were selected for the preparation of mixture. Raw materials were mixed in different proportion to make the respective organic manure mixture. Sixteen organic manure mixtures were prepared as per the treatments. The experiment was laid out in completely randomized design with 16 treatments and two replications. The results revealed that composite organic manures analyzing at least 3% N and N:K ratio of 1:0.5 were selected for further study. Five mixtures (OM3, OM5, OM9, OM11, 0M13) satisfying the selection criteria were identified for the investigation. The physical and chemical characters of selected organic manure mixture viz odour, colour , moisture content, bulk density, pH, heavy metals, EC, organic carbon, nitrogen , phosphorous and potassium contents were analyzed. The results revealed that the selected five organic manure mixtures were good quality with high N, P,K content. Shelf lives of these manures were also assessed. It was observed that theses manures retain the initial nutrient status up to 3 months and there after a reduction was observed in nutrient status. In the second experiment mineralization study was conducted in pots. The objective of the study was to assess the nutrient release pattern of different organic manure mixtures The experiment was laid out in completely randomized design with 8 treatments and three replications..Five selected mixtures along with KAU POP, KAU Adhoc organic POP and absolute control form the 8 treatments . The different composite manures were applied as N equivalent basis for the test crop amaranthus. Sampling was done at monthly interval for a period of six months after incubation. Results of the study shows that nitrogen status of all treatments in general increased up to 3 months and there after the status decreased. In general phosphorous and potassium status increased initially and then decreased. Crop response study was conducted as one pot culture investigation and another field investigation with 8 treatments and 3 replications using amaranthus as the test crop. Treatments were same as the mineralization study. Design adopted was completely randomized design for pot culture study and randomized block design for field investigation. The results revealed that among the treatments maximum yield was obtained for the treatment T5 (poultry manure- 50g, ground nut cake – 30g, rock dust- 19g and microbial consortium – 1g) and it was on par with T1 (coir pith compost – 50g, ground nut cake – 35g and ash – 15g) and T2 (poultry manure- 50g, ground nut cake – 30g, rock dust- 20g). Organic POP as well as KAU POP was significantly inferior to the best treatments. The results were same for both pot and field investigation. Maximum yield obtained under pot study was 405.29 g pot-1. Maximum yield registered in field investigation was 12.76 t ha-1. The study on economics shows that T5 registering net returns of Rs 130800/-was the most economical treatment with B:C ratio 2.2. The lowest net returns of Rs. 22200 was obtained in treatment T8 (soil alone) with B:C ratio 0.6.